(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The performance of older and young adults in a concurrent task –to read equational sentences while at the same time the subjects retain in memory three words– is comparatively studied. The purpose of the experiment is to find out if there is an effect of the variables of age, working memory, syntactic complexity and interference of a concurrent memory load processing on the comprehension of syntactically complex sentences. The multilevel statistical analysis reveals that both online processing of cleft sentences as their understanding is significantly affected by the age of participants when operating a concurrent memory load. The working memory variables and syntactical complexity, meanwhile, also significantly affect the performance of subjects, but regardless of age